Development of star tracker baffle - Chua, Jia Ying (2017)
The goal of this project is to design the star tracker’s baffle to reject stray light from entering the detector by hitting off the baffle walls. There are given lens specification to calculate out the baffle lengths and the position of the vanes. In this project, it is to find out the Sun exclusion angle for the baffles. As the larger the Sun exclusion angle, it shows that the baffle is able to block out stray light.